Pregnancy Outcomes Following Letrozole Use in Frozen-thawed Embryo Transfer Cycles: A Systematic Review and Meta-analysis - Chen, Dongjia; Shen, Xiaoting; Fu, Yu; Ding, Chenhui; Zhong, Yiping; Zhou, Canquan (Geburtshilfe und Frauenheilkunde, 2020)
While widely used for ovulation induction in assisted reproductive technology, the clinical efficacy of letrozole for endometrial preparation prior to frozen-thawed embryo transfer (FET) cycles remains yet to be elucidated. We performed a meta-analysis to compare pregnancy outcomes after letrozole use with those of other endometrial preparation protocols in patients undergoing FET. PubMed, Scopus, Embase and the Cochrane Library were searched for eligible studies. Clinical pregnancy rate (CPR), live birth rate (LBR) and birth defect rate (BDR) were analysed using odds ratio (OR) and 95% confidence interval (CI). A total of 10 studies representing 75 968 FET cycles were included. Comparable CPR and LBR were observed when comparing letrozole administration with natural cycle (OR 1.24, 95% CI: 0.69 – 2.24; OR 1.18, 95% CI: 0.60 – 2.32), artificial cycle (OR 1.46, 95% CI: 0.87 – 2.44; OR 1.39, 95% CI: 0.77 – 2.52), and artificial cycle with gonadotropin-releasing hormone agonist suppression (OR 1.11, 95% CI: 0.78 – 1.59; OR 1.18, 95% CI: 0.82 – 1.68). Pooled results of the limited studies comparing letrozole with human menopausal gonadotropin demonstrated a similar CPR between groups (OR 1.46, 95% CI: 0.29 – 7.21, two studies), but the letrozole group had a statistically lower LBR (OR 0.67, 95% CI: 0.52 – 0.86, one study). No increased BDR was observed in the letrozole group compared to natural cycles or artificial cycles (OR 0.98, 95% CI: 0.60 – 1.61; OR 1.39, 95% CI; 0.84 – 2.28). This pooled analysis supports the use of letrozole as an efficacious and safe alternative to mainstream regimens for endometrial preparation in FET cycles.
Keywords: endometrium; embryo transfer; letrozole; meta-analysis; treatment outcome